Penatalaksanaan fisioterapi pada pasien dengan osteoarthritis genue sinistra Di rsu aisyiyah ponorogo - Rahmawati, Fauziyah, Isnaini Herawati, S.Fis, S.Pd, M.Sc (2016)
Background : Osteoarthritis of the knee is abnormalities the knee joint which is non-inflammatory, non-symmertrical and not systemic pathological changes in the joint artilage and subchondral bone in th form of focal damage to the basis of bone lesions edges of the joint cartilage and joint instability that can lead to reduced joint function or until lose. Abnormality that occurs will cause clinical symptoms such as pain, joint stiffness, muscle weakness and impaired joint stability. Objective : To investigate the implementation of physiotherapy in reducing pain, increasing range of motion, increase muscle strength and improve functional activity in the case of Osteoarthritis genu of the left using the modality Infrared (IR) and Exercise Therapy (TL). Results : After treatment for 6 times the results obtained ratings of pain in the left knee pain motion, T1: 5 cm to T6: 2 cm, incrase muscle strength knee lft knee flexors T1: 4 to T6 : 4+ increase in knee extensor muscle strength left knee became T6: 0-0-130, increase range of motion knee left knee passive S: T1: 0-0-130, became T6: 0-0-135, the ability of functional activity up and down the stairs on the left knee pain does not decrease less than T1: 3 remains a T6: 3 and functional activity of a sitting to standing on the left knee pain decreased from T1: 3 to T6: 2 and a 15 meter experienced a decrease in pain of T1: 3 to T4: 2. Conclusion : From the research that has been done it has been proven with the use of Infrared and exercise therapy modality for 6 therapies associated with an increase impairment, functional limitation and disability.